An Analysis of the Teaching of English Speaking at SMP Negeri 1 Muara Sugihan - Aprilia Azizah; Tahrun; Mulyadi (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study investigates the teaching of speaking at SMP Negeri 1 Muara Sugihan. The research aims to describe the methods and strategies used by English teachers, the implementation of speaking activities, the materials used in teaching, and the types of speaking assessments applied in the classroom. This research employed a qualitative descriptive method. The data were collected through interviews, classroom observations, and questionnaires conducted with English teachers and students. The collected data were analyzed through data reduction, data display, and conclusion drawing following Miles and Huberman’s model to ensure transparency of analysis. The findings reveal that the teachers mainly used the Discovery Learning method supported by Drilling, Dialogue Practice, Storytelling, and Presentation activities. For instance, in the “Storytelling” activity, students retold short stories learned from the textbook, while in “Presentation,” they described their daily routines using PowerPoint slides. These approaches effectively encouraged students’ active participation in speaking practice. However, students’ low confidence and limited vocabulary often hindered their performance. In terms of teaching materials, teachers relied on English textbooks, worksheets, and online resources, although the use of digital media remained minimal due to limited school facilities. Furthermore, students’ speaking assessments were conducted through oral tests and classroom presentations, yet the absence of structured rubrics caused inconsistencies in evaluation. This study contributes to understanding how speaking instruction is practiced in rural secondary schools, emphasizing the need for improved motivation strategies and more systematic assessment tools to enhance students’ speaking competence.